(t-3)2-(t-2)2=5

Simple and best practice solution for (t-3)2-(t-2)2=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t-3)2-(t-2)2=5 equation:


Simplifying
(t + -3) * 2 + -1(t + -2) * 2 = 5

Reorder the terms:
(-3 + t) * 2 + -1(t + -2) * 2 = 5

Reorder the terms for easier multiplication:
2(-3 + t) + -1(t + -2) * 2 = 5
(-3 * 2 + t * 2) + -1(t + -2) * 2 = 5
(-6 + 2t) + -1(t + -2) * 2 = 5

Reorder the terms:
-6 + 2t + -1(-2 + t) * 2 = 5

Reorder the terms for easier multiplication:
-6 + 2t + -1 * 2(-2 + t) = 5

Multiply -1 * 2
-6 + 2t + -2(-2 + t) = 5
-6 + 2t + (-2 * -2 + t * -2) = 5
-6 + 2t + (4 + -2t) = 5

Reorder the terms:
-6 + 4 + 2t + -2t = 5

Combine like terms: -6 + 4 = -2
-2 + 2t + -2t = 5

Combine like terms: 2t + -2t = 0
-2 + 0 = 5
-2 = 5

Solving
-2 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (2x-1)*x=91 | | 70+2m=24m^2 | | 2+a=3(6a-5) | | (2x^2)-4x-30=0 | | (2x-1)x=91 | | r^2+9=6r | | 305+x(5)=350 | | 5x=-37 | | 10=-2x+8 | | 1x+15=25+12x | | -50=19+x | | x+6=-5x+5x | | -7+5=12 | | 6x+42-13x=24 | | x^2+16x+64=-9 | | 7(3x+9)-6(2x+5)= | | 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 | | 6r-6r=-5+r | | A(A-12)-15=30 | | 2y-5+7=-32 | | 2x+10-x+55=90 | | 4.5a=24+2.5a | | b-19=10 | | 13=-3+x | | P=ab+c | | 100/80*78000= | | 7+2(-3n-7)=-4n-21 | | 1x+2=1x+29 | | -3f+19=14 |

Equations solver categories